Integrable Deformations of Sine-Liouville Conformal Field Theory and Duality - Fateev, V.A. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
We study integrable deformations of sine-Liouville conformal field theory. Every integrable perturbation of this model is related to the series of quantum integrals of motion (hierarchy). We construct the factorized scattering matrices for different integrable perturbed conformal field theories. The perturbation theory, Bethe ansatz technique, renormalization group and methods of perturbed conformal field theory are applied to show that all integrable deformations of sine-Liouville model possess non-trivial duality properties.